SIMULASI ALIRAN FLUIDA PADA SISTEM HYDRO – MAGNETO – ELECTRIC REGENERATIVE SHOCK ABSORBER (HMERSA) DENGAN SINGLE INPUT DAN SINGLE OUTPUT - Herri Darsan; Rouhillah (J-Innovation, 2018)
The development of Hydroulic Regenerative Shock Absorber starts with presenting theories that work, and simulates them with numerical computing software to becompare with conventional shock absorber systems. The generation energy of the regenerative suspension system is only effective for high amplitude. When the amplitude is low, the generation energy will decrease as a result of bidirectional rotation and inertial losses. The greater the generator rotation, the higher current, and power generation. In the HMERSA fluid flow simulation 1 input and single output using the Fluid SIM software. the input given is 3 Hz on the hydraulic cylinder that is on the 4-wheel vehicle. The simulation was done by changing the hydraulic circuit and adding a check valve mechanism so that the rotation of the hydraulic motor becomes unidirectional. In this simulation there is no generator component because in the Fluidsim software does not provide these components in the simulation. The simulation using the Fluidsim software is intended to find out whether the hydraulic circuit that has been designed runs well marked by the rotation of the one-way hydraulic motor rotation. The design design of HMERSA with 1 input 1 output can run well marked from the rotation of the hydraulic motor into one direction when the conditions are expansion or compression. The torque value that occurs during an expansion condition is 1.1 Nm, while for the torque value that occurs when the compression condition is 1.6 Nm. The power generated from the hydraulic motor when the expansion condition is 1.6 Watt. Whereas when the compression condition of the power of the hydraulic motor that can be produced is 4 Watt.